GMAT Official Guide 2022: Book + Online Question Bank - GMAC (Graduate Management Admission Council) (John Wiley & Sons, Inc., 2021)
Study with practice questions from past GMAT(TM) exams. Your GMAT(TM) prep is comprised of comprehensive practice by studying with over 1,000 questions across quantitative and verbal reasoning, analytical writing, and integrated reasoning. Answer explanations are included so that you can study the reasoning behind the answers to help improve your performance. The questions in each section are organized by difficulty level: easy, medium and hard. Start at the beginning and work your way up to the hard questions as you build upon your knowledge.
Keywords: Language; Nonfiction